Perilaku Hygiene Organ Reproduksi Pada Remaja Putri Di Sman Olahraga Rumbai Pekanbaru - Chairil; Dien Fadilah (LPPM Universitas Muhammadiyah Riau, 2020)
Background Behavioral hygiene of reproductive organs An effort of a person (young women) in improving health by maintaining the cleanliness of reproductive organs. Purpose: This study is to determine the hygiene behavior of reproductive organs in adolescent girls at Rumbai Pekanbaru High School sports. Method: The design of this study is the sampling technique probality sampling technique, amounting to 49 respondents, data collection using a questionnaire. Results: research conducted on January 28, 2019 obtained results about that respondents in the category of good behavior are all respondents, namely 49 respondents (100%).So the hygiene behavior of female students at the Rumbai Pekanbaru high school sports is included in the category of good behavior, but there are still some students who do not use tissue after BAK, do not use cotton pants, do not change pads in one day, use narrow underwear and do not use soap, because all include hygiene behavior in maintaining the cleanliness of the reproductive organs.